Feeding ecology of the last European colobine monkey, Dolichopithecus ruscinensis. Issue 168 (July 2022) - Plastiras, Christos Alexandros; Thiery, Ghislain; Guy, Franck; Kostopoulos, Dimitris S.; Lazzari, Vincent; Merceron, Gildas
Abstract: Currently, very little is known about the ecology of extinct Eurasian cercopithecids. Dietary information is crucial in understanding the ecological adaptations and diversity of extinct cercopithecids and the evolution of this family. For example, the colobine genus Dolichopithecus is represented by multiple large-bodied species that inhabited Eurasia during the Pliocene-Early Pleistocene. The available evidence, though limited, suggests semiterrestrial locomotion, which contrasts with most extant African and Asian colobines that exhibit morphological and physiological adaptations for arboreality and folivory. These differences raise questions regarding the dietary specialization of early colobine taxa and how/if that influenced their dispersion out of Africa and into Eurasia. To further our understanding of the ecology of Plio-Pleistocene cercopithecids, we characterized the dental capabilities and potential dietary adaptations of Dolichopithecus ruscinensis through dental topographic and enamel thickness analyses on an M 1 from the locality of Serrat d'en Vacquer, Perpignan (France). We also assessed the feeding behavior of D. ruscinensis through dental microwear texture analysis on a broad sample of fossil molars from fossil sites in France, Greece, Bulgaria, and Romania. Dental topographic and enamel thickness analyses suggest that D. ruscinensis could efficiently process a wide range of foods. Results of the dental microwear texture analysis suggest that its diet ranged from folivory to the consumption of more mechanically challenging foods. Collectively, this suggests a more opportunistic feeding behavior for Dolichopithecus than characteristic of most extant colobines.